Beyond oxidative stress: Ferroptosis as a novel orchestrator in neurodegenerative disorders - Yi, Yaqiao; Jia, Pu; Xie, Peipei; Peng, Xiru; Zhu, Xuan; Yin, Shuting; Luo, Yanfang; Deng, Ying; Wan, Lifei (Frontiers in Immunology, 2025)
Neurodegenerative diseases are a group of disorders characterized by progressive loss of neuronal function due to degenerative damage to neural cells. Ferroptosis, a newly identified form of regulated cell death, is pathologically defined by iron-dependent accumulation of lipid peroxides, mitochondrial shrinkage, and increased mitochondrial membrane density. Unlike apoptosis or necrosis, ferroptosis is driven by a combination of factors, including excessive lipid peroxidation, disruption of iron homeostasis, and depletion of antioxidant defenses such as glutathione (GSH) and glutathione peroxidase 4 (GPX4). The ferroptotic process engages multiple biological functions—such as iron metabolism, lipid metabolism, oxidative stress, mevalonate signaling, transsulfuration pathways, heat shock protein activation, glutamate/cystine transport, and GSH biosynthesis. While initial studies focused on its role in cancer, accumulating evidence now links ferroptosis to neurological disorders. Ferroptosis has been implicated in the pathophysiology of stroke, traumatic brain injury, and major neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), and Huntington’s disease (HD). Several small-molecule inhibitors—including ferrostatin-1, liproxstatin-1, and iron chelators such as deferoxamine (DFO)—have demonstrated efficacy in animal models by attenuating neuronal damage and improving behavioral outcomes through the suppression of ferroptosis. In addition, natural compounds have emerged as promising candidates for targeting ferroptosis due to their structural diversity, low toxicity, and multitarget regulatory properties. These agents offer potential leads for developing novel neuroprotective therapeutics. Neurodegenerative diseases remain a significant global health burden, with limited effective treatments available to date. Modulation of ferroptosis presents a new conceptual framework for therapeutic intervention, offering hope for disease-modifying strategies. This review summarizes recent advances in understanding the role of ferroptosis in neurodegenerative disease mechanisms, focusing on its contribution to pathological progression, molecular regulation, and therapeutic interventions. By integrating current findings, we aim to provide theoretical insights into novel pathogenic mechanisms and scientific guidance for the development of targeted therapies that modulate ferroptosis to slow or halt disease progression.